RASIO-RASIO YANG BICARA: APAKAH PT PP (PERSERO) TBK MASIH LAYAK DISEBUT RAKSASA KONSTRUKSI? - Indah Puspita Sari; Anindyarta Adi Wardhana; Imam Arie Mulyanto; Ovalia Rukmana (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
PT PP (Persero) Tbk is a state‑owned construction enterprise recognized as a cornerstone of national infrastructure development in Indonesia. Challenges such as cash flow constraints, rising indebtedness, and declining profitability have underscored the urgency of assessing its competitive resilience and long‑term sustainability. This study aims to evaluate the financial performance of PT PP (Persero) Tbk by employing profitability, liquidity, and leverage, and to determine whether the company remains worthy of its status as one of the nation’s construction giants. A qualitative, descriptive approach was utilized, drawing upon secondary data sourced from the company’s official website and the Indonesia Stock Exchange (IDX). Data were collected through documentation, and descriptive analyses were conducted to identify patterns and trends in the company’s financial performance over time. The results reveal that while the company has demonstrated a generally favorable trend in profitability ratios, certain challenges persist in optimizing net income. Liquidity ratios indicate improvements in cash and current ratios, suggesting enhanced short‑term financial resilience. Meanwhile, although the debt‑to‑equity ratio has shown signs of recovery, the capital structure remains constrained by interest‑bearing liabilities, necessitating a more selective and strategic approach to debt management to safeguard long‑term financial stability. Overall, this study concludes that PT PP (Persero) Tbk remains a viable and competitive entity, meriting its designation as one of Indonesia’s leading construction firms from a financial performance perspective.